2013
DOI: 10.1055/s-0033-1349063
|View full text |Cite
|
Sign up to set email alerts
|

Pilotprojekt einer pädiatrischen Antibiotic-Stewardship-Initiative am Dr. von Haunerschen Kinderspital - neue Wege der pädiatrischen Infektiologie

Abstract: The steady increase in antimicrobial resistance is of growing concern in healthcare. Antibiotic Stewardship [ABS] Strategies are important tools to control antibiotic use and -prevent antimicrobial resistance. An increasing number of institutions are developing ABS initiatives also in pediatrics. However, few data are available assessing the implementation and efficiency of these pediatric ABS programs.At the Dr. von Hauner Children's Hospital, Ludwig-Maximilian University, a tertiary care pediatric reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
(11 reference statements)
0
6
0
3
Order By: Relevance
“…Eighteen papers (18/113, 15.9%)[40-42, 51, 54, 60, 71, 85, 87, 91, 98, 105, 106, 125, 135, 136, 138, 142] showed an increase in compliance among prescribing physicians; half of the papers analysing this outcome were from USA and Canada (10/18, 55.5%), and the main ASPs adopted were guidelines (9/34, 26.5%)[40,42,54,60,85,87,91,106,125,142], doctors education (5/34, 14.7%)[54,91,98,138,142] and other not common ASPs such as antibiotic order set[42,51], and checklists[87,91]. Sixteen of the included studies[16/113, 14.2% in total; 7/16 (43.7%) from USA, 6/16 (37.5%) from Asia and the rest (18.7%) from Europe] quantified cost savings related to the intervention[39,49,52,64,66,69,73,86,89,92,97,101,102,[122][123][124]. Decreases in costs were most often due to lower rates of drug administration.…”
mentioning
confidence: 99%
“…Eighteen papers (18/113, 15.9%)[40-42, 51, 54, 60, 71, 85, 87, 91, 98, 105, 106, 125, 135, 136, 138, 142] showed an increase in compliance among prescribing physicians; half of the papers analysing this outcome were from USA and Canada (10/18, 55.5%), and the main ASPs adopted were guidelines (9/34, 26.5%)[40,42,54,60,85,87,91,106,125,142], doctors education (5/34, 14.7%)[54,91,98,138,142] and other not common ASPs such as antibiotic order set[42,51], and checklists[87,91]. Sixteen of the included studies[16/113, 14.2% in total; 7/16 (43.7%) from USA, 6/16 (37.5%) from Asia and the rest (18.7%) from Europe] quantified cost savings related to the intervention[39,49,52,64,66,69,73,86,89,92,97,101,102,[122][123][124]. Decreases in costs were most often due to lower rates of drug administration.…”
mentioning
confidence: 99%
“…A recently published systematic scoping review on antibiotic stewardship in pediatrics [ 11 ] reported that so far only eight studies focused on PAP. Six showing an improvement in antibiotic usage appropriateness after PAP guideline implementation [ 4 , 5 , 6 , 12 , 13 , 14 ], one not reporting any change in PAP adherence after a checklist and antibiotic order list implementation [ 7 ], and one [ 15 ] reporting no significant changes in hospital-associated infection rate nor in multidrug-resistant organism rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to assess the impact of ASP implementation on broad-spectrum antimicrobials administration in one of the largest and referral pediatric hospitals in Isfahan, Iran. According to previous studies, 3.4 -3.5% of antimicrobial prescriptions in pediatric patients were noted to be unnecessary and over-prescribed (16,17). Due to inappropriate prescription and consumption of antibiotics, the number of multidrug resistant pathogens like pseudomonas aeroginosa is increasing, and critical restrictions like implementing practical guide antibiotic stewardship is essential for managing this problem (18,19).…”
Section: Discussionmentioning
confidence: 99%